Determinants of consumer demeanors with regard to halal food - Md Sawari, Siti Salwa; Ghazali, Mohd Al'Ikhsan; Jumahat, Tajulashikin (Elite Hall Publishing House, 2020)
Previous research has shown consumers to be highly aware towards halal food production in Malaysia. However, little research has tried to investigate determinants of consumer demeanors with regard to halal food. The paper presents the results of a survey which was carried out in Malaysia to investigate the formation of consumer demeanors towards halal food production. This study involved 150 Muslim consumer in Malaysia. All respondents completed a set of self-developed questionnaire. The tools for statistical analysis employed in this study were descriptive, and confirmatory factor analysis (CFA) using IBM SPSS 20.0. Results show that Malaysian consumers turned out to be significantly have positive demeanor towards halal foods. The pattern matrix revealed that 17 items were loaded into four determinants; attitude, perceived behavioural control, subjective norm and religious belief. Overall, the present study has given a meaningful information to all consumers about halal food, therefore it is a valuable guideline for them to choose the right food in the market.